Cost-Benefit Analysis of Buildings Retrofitted Using GIB Systems. Issue 2 (May 2016) - Beigi, Hossein Agha; Christopoulos, Constantin; Sullivan, Timothy J.; Calvi, Gian Michele
Recently, the gapped-inclined brace system (GIB) has been developed as an effective retrofitting solution for soft-story buildings. This paper presents a cost-benefit study of a building retrofitted using the GIB system. A six-story, reinforced concrete (RC) frame with an open story at the ground level and masonry infills on all other floors is studied. To investigate the effectiveness of alternate retrofit configurations, different scenarios of GIB systems are numerically analyzed, expected repair costs for various levels of seismic intensity are computed, and cost benefit values are compared to each other and to those obtained when the building is strengthened and stiffened at the ground floor using conventional methods. Results show that GIB retrofit solutions are likely to represent significant cost benefits compared to traditional retrofit solutions. The results also indicate that GIBs do not need to be positioned at all column locations of the soft story, which could be beneficial in reducing the overall retrofit cost and improving architectural functionality of the retrofitted structure.